2012
DOI: 10.1007/s00192-012-1667-5
|View full text |Cite
|
Sign up to set email alerts
|

New approach in vaginal prolapse repair: mini-invasive surgery associated with application of platelet-rich fibrin

Abstract: The use of PRF for site-specific prolapse repair is associated with a good functional outcome because of the healing and mechanical properties of PRF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 30 publications
2
16
0
Order By: Relevance
“…29,31 However, no difference in cell colonization was observed in our model in the presence of L-PRF. In clinical studies, L-PRF seems to facilitate the regeneration of soft tissues, [39][40][41] suggesting an effect on fibroblast migration or proliferation. Again, this effect was not observed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…29,31 However, no difference in cell colonization was observed in our model in the presence of L-PRF. In clinical studies, L-PRF seems to facilitate the regeneration of soft tissues, [39][40][41] suggesting an effect on fibroblast migration or proliferation. Again, this effect was not observed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Several papers compare and contrast PRP and leukocyte and platelet-rich fibrin (L-PRF) [212] or PRP, cryoprecipitate, and thrombin with commercial fibrin sealants [207] finding influences of leukocytes on growth factor efficacy and similar clot strengths, respectively. Several clinical articles discuss using PRP in a variety of surgical specialties: cardiac [213], general [213], gynecologic [213], rhytidectomy [206], and vaginal prolapse [208]. Finally, a review of both PRP and platelet-rich fibrin (PRF) was published [205].…”
Section: Less Frequently Published Clinical Applications Of Fibrinmentioning
confidence: 99%
“…32 Earlier feasibility study on a small number of patients by Einarsson et al, 33 however, revealed that autologous platelet gel application during the regular anterior colporrhaphy did not increase the durability of the surgical repair. Recent study by Gorlero et al 34 indicates that the use of platelet-rich fibrin (PRF) for site-specific prolapse repair is associated with a good functional outcome (follow-up at 24 months) because of the healing and mechanical properties of PRF. Thus, these in vivo clinical results support the safety and potential effectiveness of platelet enriched materials (PRP or PRF), in the field of urogynecology.…”
Section: Discussionmentioning
confidence: 98%